The Impact of Digitalization on Improving Vocational Skills Mastery for Learning Disabilities Special Education Needs Students (SENs): A Literature Review Analysis - Ayaoo, Dhevendren; Gunarhadi, Gunarhadi; Yasin, Mohd Hanafi bin Mohd; Subagya, Subagya (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This literature review analysis explores the growing use of digital tools in vocational training programs for students with learning disabilities (LD). Through a review of literature (2014-2024), more than 20 articles related to the topic, examines the potential of digital tools to address the specific learning challenges faced by students with LD and improve their vocational skill mastery. This analysis is expected to reveal the effectiveness of various digital tools such as simulations, gamified learning platforms, and personalized learning technologies. While the research suggests promise in improved skill acquisition, enhanced engagement, and development of essential workplace skills, challenges like teacher training and accessibility concerns are also identified. Emerging trends in the use of virtual reality, artificial intelligence, and gamification for personalized learning are explored, highlighting the potential for further advancements in this field. Overall, the analysis underscores the significant role digital tools can play in creating more inclusive and effective vocational training programs, ultimately empowering students with LD to achieve successful career outcomes.